Strategi dan Struktur Nafkah Rumah Tangga Petani Suku Buton Di Dusun Kahena Desa Batu Merah Kecamatan Sirimau Kota Ambon - Rumalean, Trisna D; Siwalette, Jeter D; Puttileihalat, Paulus M (Jurnal Agrosilvopasture-Tech, 2025)
This type of research is carried out using a qualitative approach. The location of this research is in Kahena Hamlet, RT. 007/RW. 017, one of the hamlets in Batu Merah Village, Sirimau District, Ambon City. The livelihood strategy is an activity undertaken by farmers to meet their basic living needs and enhance the quality of their lives. The choice of livelihood pattern is determined by the availability of resources and the ability to access various sources of income. The three sources of livelihood are: on-farm (income from one’s own land), off-farm (income from work outside one’s own land), and non-farm (income from private businesses). Farmer household expenses are the total money that farmer households spend to meet their living needs. The cost in this study is divided into two, namely routine costs and non-routine costs.